Bayo Lapawol (Let Their Voices Be Heard): Haitian Women's Barriers to and Facilitators of Cervical Cancer Prevention and Control. (December 2021) - Moise, Rhoda K.; Jonas, Eddy; Campa, Elizabeth M.; Clisbee, Mary; Lopes, Gilberto; Kobetz, Erin
This study aimed to increase understanding of barriers to cervical cancer prevention and control in Haitian women using photovoice methodology. Consented participants were (1) trained to use a digital camera and encouraged to capture their screening barriers, (2) interviewed to unpack and analyze their images, and (3) invited to participate in follow-up focus groups for refined discussion and data triangulation for content analysis using NVivo software. The sample included women ( n = 25) who were on average 42 years ( SD = 9.8, range: 26–57) and born and raised in Haiti. Results highlighted multiple barriers, including gendered family responsibilities, concerns about quality of care, financial and time constraints, worries about discomfort and exam efficacy, and emotional deterrents such as frustration. Framed by the PEN-3 model's dimensions of cultural identity, relationships and expectations, and cultural empowerment, women's recommendations to overcome barriers spanned education, evaluation, and empowerment, respectively, across individual, interpersonal, and institutional systems. Study results call for more extensive examination of the diversity present in the groups of African origin to unearth transnational, multifaceted determinants of health by biology, beliefs, and behaviors including sociocultural and socioenvironmental access. Future interventions must include development of proactive policies, which deliberately pressure the government and global community to prioritize health infrastructure while simultaneously educating women about and dispelling fear of cervical cancer, thus empowering Haitian women to live their healthiest lives. Accordingly, this study may contribute to understanding global health equity advances and improving public health infrastructure in underresourced settings in low- and middle-income countries in the Caribbean.